Draw the lightning down : Benjamin Franklin and electrical technology in the Age of Enlightenment - Schiffer, Michael B. (University of California Press, 2003)
Exploring the major role Benjamin Franklin played in laying the foundations of modern electrical science and technology, this text is rich with historical details and anecdotes. The story brings to light the arcane and long-forgotten inventions that made way for many modern technologies.